Exploring consumer boycott intelligence towards Israel-related companies in Malaysia: An integration of the theory of planned behaviour with transtheoretical stages of change. Issue 1 (12th October 2018) - Hamzah, Hanizah; Mustafa, Hasrina
Abstract : Purpose: Drawing on the transtheoretical model (TTM) into the theory of planned behaviour (TPB) framework, this study aims to understand the factors affecting the intention of Malaysian consumers to boycott products and services from companies perceived to be supporting or funding Israel and identify specific TPB variables that are important at each stage of change. Design/methodology/approach: Data collected were based on an online survey among 177 respondents working in Malaysian conglomerates based in Kuala Lumpur. Findings: The results show moderate intention to participate in the boycott among the respondents with attitude towards boycott, subjective norm and perceived behavioural control of boycott have significant relationship with intention to participate in the boycott towards Israel. The study also found significant linear increases of TPB constructs across the stages of change, which indicated significant influence of all TPB constructs at each stage of change. Originality/value: Consumer boycott is not unheard of in Malaysia, but empirical research in the area is still lacking. As markets expand, the consumers also evolve to become more knowledgeable and ethical in their consumption, sometimes choosing to boycott to coerce the companies or brands to be environmentally, ethically and socially responsible. Findings from this study are expected to benefit NGOs or associations that intend to develop more effective campaigns to encourage consumers to use boycott to drive social or ethical causes.